Attentional responses to the color exposure sequence of landscape paintings: evidence from fNIRS and eye-tracking - Jeong, Hyoyeong; Kim, Seongdae (Frontiers in Human Neuroscience, 2025)
IntroductionColor is a critical determinant of esthetic experience, shaping both immersion and cognitive responses. However, the extent to which the sequence of color exposure modulates the interplay between neural activation and ocular behavior remains insufficiently understood.MethodsTen chromatic landscape paintings were collected and converted into achromatic versions, yielding a total of 20 visual stimuli. Participants were assigned to two conditions: Condition A (achromatic to chromatic) and Condition B (chromatic to achromatic). Visual attention and prefrontal activation were assessed using eye-tracking techniques and functional near-infrared spectroscopy.ResultsAnalyses revealed significantly greater neural activation in Condition A within the left dorsolateral prefrontal cortex (p-raw = 0.006), left orbitofrontal cortex (p-raw = 0.043), and right orbitofrontal cortex (p-raw = 0.043). Eye-tracking metrics indicated longer Total duration of fixation (p-raw = 0.015), Maximum duration of fixation (p-raw = 0.036), and Total duration of whole fixation (p-raw = 0.025) under Condition A. Subjective evaluations also showed significant differences, with higher ratings for Match (p-raw = 0.005) and Feel (p-raw = 0.029).DiscussionThese findings demonstrate that color stimuli exert a decisive influence not only on subjective immersion but also on objective neurocognitive processes. The study extends the scientific foundation of empirical esthetics and offers novel implications for the design of museum and exhibition environments.